Jawapan

2016-03-07T12:43:46+08:00
(3)2+k(3)+5=0                                                                                                  6+3k+5 =0                                                                                                      11+3k=0                                                                                                          3k = -11                                                                                                          -11/3 = k     
2016-03-07T12:54:06+08:00
H(x) = x^2 +kx + 5

h(3)
= 3^2 + 3(k) + 5
= 9 + 3k + 5
= 14 + 3k

katakan h(3) = 0
14 + 3k = 0
3k = -14
k = -14/3
k = -4 2/3